Comprehensive Quality Principles as A Contribution to The Development of Premier League Club Management in Libya - Alhaaj, Mohammed; Boukari, Samia; Attia, Ahmed; Mhenni, Thouraya; Rime, Sioud; Salameh, Hamed; Khalifa, Riadh (Advances in Social Sciences Research Journal, 2024)
The research aims to develop administrative work in Premier League clubs in Libya by applying the principles of overall quality. In this research, the descriptive method was used depending on the nature of the research. The study population included members of the boards of directors of Premier League clubs, which had twenty (20) clubs registered with the Libyan Football Federation for the 2023-2024 sporting season. The research sample was selected from members of the boards of directors of twenty (20) professional sports clubs of the Premier League in Libya, including fourteen (14) board chairmen, fifteen (15) treasurers and forty-seven (47) board members responded. The results of this research showed that there are statistically significant differences between the frequencies of responses of the research sample members in all the statements of the first axis titled “The extent of officials’ awareness of the concept and philosophy of comprehensive quality in Premier League clubs” and the second and third axes titled respectively “The extent to which senior management in Premier League clubs is centered around the beneficiaries to achieve their needs, desires, and expectations”; “The style of administrative leadership that must be implemented in the Premier League clubs in Libya” , in favor of the most frequent response. Regarding the questionnaire, the arithmetic mean was 2.54, with a relative importance of 84.8%, and the response direction was (high) on the principles of comprehensive quality for developing administrative work in the Premier League clubs in Libya. The researcher recommends the necessity of using the principles of comprehensive quality in sports clubs in order to develop their administrative work, as well as asking the responsible authorities to establish a special center for comprehensive quality in the sports field for continuous development and improvement.